Successional soil acidification links bacterial community shifts to nitrogen-cycling gene potential in a subalpine spruce chronosequence - Hangyu Bai; Bingjin Wang; Xiuling Yang; Shunzhi Xue; Wenyuan Li; Caishun Qi; Kun Ma; Dengwu Li (Applied Soil Ecology, 2026)

From molecular interactions to functional enhancement: unraveling the non-covalent binding between Perilla seed protein fibrils and structurally diverse polyphenols - Xiquan Li; Shaohua Chen; Guangyu Xu; Xiuling Zhang; Zhili Pan; Weiwei Yang (Food Research International, 2026)

Computational modeling of prefrontal-amygdala circuits links functional connectivity alterations to circuit-level mechanisms in major depression - Licong Li; Fukuan Zhang; Shuaiyang Zhang; Jinzhao Wei; Kun Wang; Bote Zheng; Jianli Yang; Xiuling Liu (Journal of Computational Neuroscience, 2026)

The synergistic effects of co-exposure of water disinfection byproducts DCBQ and DBBQ on lipid metabolism of mice - Ziqiao He; Xue Han; Tianyue Zhang; Yuewen Yang; Minghan Jiang; Xu Zhang; Haiying Du; Rifeng Lu; Xiuling Song; Jinhua Li (Chemico-Biological Interactions, 2026)

A lightweight two-stage framework for headland navigation area localization and path extraction in cornfields - Yuting Zhai; Jian Li; Xiuling Yu; Yang Zhou; Yanlei Xu (Precision Agriculture, 2026)

Green plasticization of soy protein isolate based films by β-cyclodextrin and lactic acid supramolecular eutectic solvent: active packaging performance and blueberry preservation - Bailiang Zheng; Jiale Lv; Jun Yang; Xiuling Zhang; Wentao Zhang; Tiezhu Li (Food Hydrocolloids, 2026)

Rhizosphere microbial diversity and community assembly in tree species–slope aspect coupled mountain forests of the Qilian Mountains, northeastern Qinghai–Tibet Plateau - Hangyu Bai; Qian Chen; Xiuling Yang; Dengwu Li (Applied Soil Ecology, 2026)

Characteristics of sediment microbial community structure under different vegetation types with various restoration durations in Hongze Lake - Yuhan Jin; Wangting Yang; Yuling Yang; Yanping Wang; Huaiping Ling; Sile Wen; Bingjie Ren; Xiuling Zhang; Zhenfa Su; Jinghao Jin; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

The GRAPE selection escapes from slow in planta directed evolution - Xiuling Yang; Wei Guo; Shaoshuang Sun; Xueping Zhou (Molecular Plant, 2026)

Chitosan/gelatin-based film activated by Pickering emulsion of citrus essential oil stabilized by esterified starch/whey protein isolate fibrils: Application in preserving freshness of blueberry - Run Ji; Hao Guo; Xu Yang; Lepei Wang; Xiuling Zhang; Hui Zhang (Food Chemistry, 2026)

Acidic-heating induced protein fibrils derived from perilla seed residues: spotlight on assembly behavior, conformational changes and structure-function relationships - Xiquan Li; Jun Yang; Liting Feng; Hao Guo; Xiaochen Liu; Xiuling Zhang; Wentao Zhang (Food Hydrocolloids, 2026)

YIP: optimized YOLOv11-seg for accurate intramuscular fat percentage prediction in pigs using non-invasive ultrasound imaging - Junhao Zhang; Hang Jiao; Genyuan Li; Hanhan Li; Chenglin Li; Pengsheng Dong; Yan Liu; Bo Jiang; Peng Shang; Feng Yang; Chunli Li; Xinjian Li; et al. (Science China Life Sciences, 2026)

Silica Nanoparticles Induce BV-2 Cells Autophagy Via activation of NLRP3 inflammasome and CaMKK2 Signaling Pathways - Tianxiang Liu; Mingqian Wang; Yuanyuan Zhang; Li Yang; Jia Zhang; Hongzhu Wei; Xinyue Li; Huan Pang; Jiali Li; Zhixuan Luo; Mengyue Liu; Haiying Du; et al. (Molecular Neurobiology, 2026)

A Novel Palmitoylation-Related Molecular Signature for Predicting and Therapeutically Targeting Alzheimer’s Disease - Xiuling Miao; Kaiyu Luo; Yinglei Li; Yang Zhou; Meng Wei; Ting Zhang; Yazhuo Hu; Heran Wang; Jianjun Jia (Molecular Neurobiology, 2026)

Biodegradable multifunctional hyaluronic acid hydrogel microneedle band-aids for accelerating skin wound healing - Erman Zhao; Xiuling Tang; Minggao Zhao; Le Yang (Drug Delivery and Translational Research, 2026)

Engineering resistance genes against tomato brown rugose fruit virus - Junzhu Wang; Tianxin Shen; Mengjie Song; Jiayi Fan; Yiqing Li; Toto Zen Chin; Yidan Yu; Fan Huang; Xiuling Yang; Changbao Li; Xueping Zhou; Chuanyou Li; et al. (Science China Life Sciences, 2025)

Woody Plant Encroachment Significantly Alters Grassland Soil Microbial Community: A Global Meta‐Analysis - Guoliang Sha; Shuyan Chen; Xuanchen Liu; Wanyu Xia; Hanwen Cui; Anning Zhang; Lizhe An; Zi Yang; Xia Zhao; Jing Zhang; Xiuling Yu; Jing Xiao; et al. (Global Ecology and Biogeography, 2025)
Aim Woody plant encroachment is reshaping grassland ecosystem functions worldwide. While its aboveground impacts are well documented, how this process alters microbial communities—key drivers of belowground processes—remains poorly understood. We aimed to (1) quantify the general effects of global woody plant encroachment on soil microbial community attributes in grasslands and (2) identify the abiotic and biotic factors driving these changes. Location Global grassland ecosystems. Time Period 2000–2024. Major Taxa Studied Soil microbial communities (bacteria, fungi). Methods We conducted a meta‐analysis of 241 paired observations to evaluate changes in microbial composition, diversity, biomass, activity and enzyme activity under woody plant encroachment. Results Woody plant encroachment significantly altered soil properties. Woody plant encroachment also promoted a comprehensive increase in microbial community diversity, biomass, microbial activity and enzyme activity, as well as changes in community composition. The nitrogen‐fixing status of the encroaching species (biotic factor) significantly affected microbial responses: encroachment by nitrogen‐fixing plants resulted in a higher abundance of Bacteroidetes, fungal richness, microbial biomass phosphorus and phosphatase activity compared to non‐nitrogen‐fixing plants. In addition, abiotic factors, such as mean annual temperature, soil organic carbon and total nitrogen were identified as key factors driving microbial responses. Specifically, mean annual precipitation, mean annual temperature and elevation jointly regulated the effects of woody plant encroachment on soil microbial community attributes by influencing plant and soil properties. Main Conclusions This meta‐analysis demonstrated that woody plant encroachment significantly reshaped soil microbial communities in grassland ecosystems. Our findings highlight the role of abiotic factors (climate, elevation, organic carbon and total nitrogen), and biotic factors (nitrogen‐fixing status) in mediating the response of soil microbial communities. These insights contribute to a better understanding of belowground ecological processes and provide valuable guidance for grassland management and predictions of biogeochemical cycles under global change.

Preparation and characterization of highly stable pH-sensitive multifunctional films based on co-pigment-anthocyanin conjugate system for pork monitoring and preservation - Shuang Song; Run Ji; Jieli Xu; Xiyue Yang; Qiyun An; Xiuling Zhang; Wentao Zhang (Food Hydrocolloids, 2025)

Air heating-alkaline hydrothermal production of artificial humic acid: Rapid and efficient humification of waste biomass - Bo Yang; Jiliang Zheng; Yiwei Sun; Xinyu Chen; Xiuling Yan; Bekchanov Davronbek; Jinxiong Wu; Patrycja Boguta; Lijuan Zhang; Junli Ren; Xintai Su (Journal of Environmental Chemical Engineering, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

Oxygen-vacancy-rich Ni/CeO2: UiO-66-derived high-efficiency catalyst for low-temperature CO2 methanation - Yidan Li; Yahui Yang; Zhenzhen Huang; Huilin Zhou; Riying Zeng; Xiaohan Lin; Xiuling Ma; Lihua Wang; Shengchang Xiang; Zhangjing Zhang (Chemical Engineering Journal, 2025)

Efficient preparation of potassium humate from waste vegetable leaves: Development of a Cu2O@HAK catalyst and innovative application of hydrothermal method - Jiamin Qi; Jiliang Zheng; Yatang Dai; Bo Yang; Haohao Bian; Xinyu Chen; Shunyu Yin; Xiuling Yan; Xiaoyan He; Hongguang Zhao; Yanjie Ren; Changchun Ge; et al. (Journal of Environmental Chemical Engineering, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

Computational Modeling of the Prefrontal-Cingulate Cortex to Investigate the Role of Coupling Relationships for Balancing Emotion and Cognition - Jinzhao Wei; Licong Li; Jiayi Zhang; Erdong Shi; Jianli Yang; Xiuling Liu (Neuroscience Bulletin, 2025)

Accelerating peroxymonosulfate activation over fiber-shaped Fe@Fe3C/CNF for ultrafast tetracyclines degradation: Active site synergy and mechanisms - Man Yang; Yafan Lu; Wenjuan Zhang; Long Xie; Junjie Tian; Yiliyasi Baikeli; Fang Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Mika Sillanpää; Longlong Geng (Journal of Environmental Chemical Engineering, 2024)

Triggering efficient redox cycling and electron transporting in CuCo spinel oxides via oxygen vacancy building for rapid degradation of antibiotics - Longlong Geng; Fengting Geng; Xianghan Cheng; Man Yang; Xiaoli Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Wenyuan Han; Shujuan Zhuang; Yuting Chen; Guangzhi Hu (Chemical Engineering Journal, 2024)

The effects of climate and soil depth on living and dead bacterial communities along a longitudinal gradient in Chile - Xiuling Wang; Lars Ganzert; Alexander Bartholomäus; Rahma Amen; Sizhong Yang; Carolina Merino Guzmán; Francisco Matus; Maria Fernanda Albornoz; Felipe Aburto; Rómulo Oses-Pedraza; Thomas Friedl; Dirk Wagner (Science of The Total Environment, 2024)

NaCl improves the vegetable quality of Mesembryanthemum crystallinum Linn. by increasing betacyanin and nutrient contents - Yanlu Liu; Qing Liu; Xiuling Liu; Yang Zhao; Yun Liu; Baoshan Wang; Min Chen (Plant and Soil, 2024)

Multi-scale modeling to investigate the effects of transcranial magnetic stimulation on morphologically-realistic neuron with depression - Licong Li; Shuaiyang Zhang; Hongbo Wang; Fukuan Zhang; Bin Dong; Jianli Yang; Xiuling Liu (Cognitive Neurodynamics, 2024)

Bimetallic peroxide nanocatalytic gel for water disinfection - Yang Guo; Zhihui Niu; Jianyu Huang; Yingying Ding; Xiuling Li; Yuanda Song; Guangwu Wen; Xiaowei Li (Journal of Environmental Chemical Engineering, 2024)

Diversity and functional traits of seed endophytes of Dysphania ambrosioides from heavy metal contaminated and non-contaminated areas - Weijun Gong; Qiaohong Li; Yungui Tu; Dian Yang; Yibin Lai; Wenting Tang; Wenqin Mao; Yue Feng; Li Liu; Xiuling Ji; Haiyan Li (World Journal of Microbiology and Biotechnology, 2024)

Fabrication and characterization of blue honeysuckle anthocyanins-loaded nanocomposite films and the application in pork preservation - Jiaxu Li; Xinhua Zhang; Jiale Lv; Jun Yang; Xiaochen Liu; Xiuling Zhang; Wentao Zhang (Food Hydrocolloids, 2024)

Boosting the feasibility of heterogeneous telomerization of 1,3-butadiene with methanol by low-surface-area N-heterocyclic carbene-functionalized hypercrosslinked polymers - Xichao Zhang; Bo Yu; Yuanjun Zhao; Xiuling Guo; Zihao Yang; Xin Ding; Yong Yang (Chemical Engineering Journal, 2024)

Proteomic analysis of boar sperm with differential ability of liquid preservation at 17 °C - Chenglei Song; Zhe Zhang; Yilin Wei; Yaqing Dou; Kunlong Qi; Xiuling Li; Feng Yang; Xinjian Li; Kejun Wang; Ruimin Qiao; Xuelei Han (Theriogenology, 2024)

Magnetic dendritic mesoporous silica nanoparticles based integrated platform for rapid and efficient analysis of saccharides - Xiuling Zhao; Jiacheng Dong; Yaqian Zhang; Tianrun Wu; Zijun Bie; Yang Chen (Analytica Chimica Acta, 2024)

Nanoparticle (NP)-mediated APOC1 silencing to inhibit MAPK/ERK and NF-κB pathway and suppress breast cancer growth and metastasis - Shaomin Liu; Fengqian Zhang; Yixia Liang; Guo Wu; Rong Liu; Xiuling Li; Phei Er Saw; Zhonghan Yang (Science China Life Sciences, 2023)

Boosting C2+ production from photoelectrochemical CO2 reduction on gallium doped Cu2O - Xiuling Guo; Cong Wang; Zihao Yang; Yong Yang (Chemical Engineering Journal, 2023)

Unraveling source-to-sink dust transport in Central and East Asia by identifying provenances of aeolian sediments - Yue Li; Peng Liang; Yougui Song; Xinzhou Li; Shengli Yang; Xiuling Chen; Xiulan Zong; Nosir Shukurov; Yudong Li (Atmospheric Research, 2023)

A rapid and effective method for obtaining ardicrenin from Ardisia crenata Sims var. bicolor plants - Zhen Lin; Xiuling Yang; Lin Li; Chunyan Ma; Lingjuan Kong; Huancheng Li; Shican Xiong; Haiyan Zhong; Shangrao Pu; Fang Liang; Ju Hu (Brazilian Journal of Botany, 2023)

Facile one-pot synthesis of multifunctional tetracycline hydrochloride nanoparticles with high stability and photothermal effect for synergistically improved antibacterial performance and sustainability - Mingzhou Lu; Weitao Wang; Xiuling Fang; Yang Xuan; Liying Chen; Xiaojing Wang; Jianhao Wang; Cheng Wang (Sustainable Chemistry and Pharmacy, 2023)

Estrogen upregulates DNA2 expression through the PI3K-AKT pathway in endometrial carcinoma - Xinyan Wang; Xiuling Xu; Ting Zhang; Yang Jin; Sheng Xu; Lifeng Chen; Yucheng Lai; Ling Zhang; Ruolang Pan; Yan Yu (Journal of Zhejiang University-SCIENCE B, 2023)

The star target in SLE: IL-17 - Yi Yang; Chen Yan; Le Yu; Xiuling Zhang; Jingjing Shang; Jie Fan; Rongwei Zhang; Jie Ren; Xinwang Duan (Inflammation Research, 2023)

Hybrid histidine kinase HisK2301 modulates carotenoid production to counteract cold-induced oxidative stress in Rhodosporidium kratochvilovae YM25235 under low temperature - Meixia He; Xiaoxia Yang; Tao Liu; Xiaoqing Zhang; Xiuling Ji; Yunlin Wei; Qi Zhang (Antonie van Leeuwenhoek, 2022)

Occurrence and distribution of geminiviruses in China - Fangfang Li; Rui Qiao; Zhanqi Wang; Xiuling Yang; Xueping Zhou (Science China Life Sciences, 2022)

The Sm gene conferring resistance to gray leaf spot disease encodes an NBS-LRR (nucleotide-binding site-leucine-rich repeat) plant resistance protein in tomato - Huanhuan Yang; Hexuan Wang; Jingbin Jiang; Mingyue Liu; Zengbing Liu; Yinxiao Tan; Tingting Zhao; He Zhang; Xiuling Chen; Jingfu Li; Aoxue Wang; Minmin Du; et al. (Theoretical and Applied Genetics, 2022)

Three Dimensional Statistical Damage Constitutive Model of Rock Based on Griffith Strength Criterion - Song Chen; Xiuling Cao; Zhao Yang (Geotechnical and Geological Engineering, 2021)

Calculation method and statistical characteristics of loosening pressure of a shallow-buried long-span tunnel in composite rock layer with random joint network - Song Chen; Xiuling Cao; Chunsheng Qiao; Zhao Yang; Chaozheng Qiao (Arabian Journal of Geosciences, 2021)

Chemical constituents from Glehnia littoralis and their chemotaxonomic significance - Shouwen Zhang; Fang Cheng; Li Yang; Jinxiang Zeng; Fengyu Han; Xiuling Yu; Yuye Zhu; Guoyue Zhong; Junwei He (Natural Product Research, 2020)

DCLK1 inhibition attenuates tumorigenesis and improves chemosensitivity in esophageal squamous cell carcinoma by inhibiting β-catenin/c-Myc signaling - Lianqun Zhang; Shengli Zhou; Ertao Guo; Xiaoqi Chen; Jun Yang; Xiuling Li (Pflügers Archiv - European Journal of Physiology, 2020)

Exposure to copper altered the intestinal microbiota in Chinese brown frog (Rana chensinensis) - Yijie Yang; Xiuling Song; Aixia Chen; Hongyuan Wang; Lihong Chai (Environmental Science and Pollution Research, 2020)

Rock paper scissors: CRISPR/Cas9-mediated interference with geminiviruses in plants - Xiuling Yang; Huanbin Zhou; Xueping Zhou (Science China Life Sciences, 2019)

Physiological and RNA-seq analyses provide insights into the response mechanism of the Cf-10-mediated resistance to Cladosporium fulvum infection in tomato - Guan Liu; Junfang Liu; Chunli Zhang; Xiaoqing You; Tingting Zhao; Jingbin Jiang; Xiuling Chen; He Zhang; Huanhuan Yang; Dongye Zhang; Chong Du; Jingfu Li; et al. (Plant Molecular Biology, 2018)

Fine-mapping qFS07.1 controlling fiber strength in upland cotton (Gossypium hirsutum L.) - Xiaomei Fang; Xueying Liu; Xiaoqin Wang; Wenwen Wang; Dexin Liu; Jian Zhang; Dajun Liu; Zhonghua Teng; Zhaoyun Tan; Fang Liu; Fengjiao Zhang; Maochao Jiang; et al. (Theoretical and Applied Genetics, 2017)

Upregulation of hydroxysteroid sulfotransferase 2B1b promotes hepatic oval cell proliferation by modulating oxysterol-induced LXR activation in a mouse model of liver injury - Zhengyang Wang; Xiaoming Yang; Liang Chen; Xiuling Zhi; Hanyu Lu; Yanxia Ning; Joe Yeong; Sifeng Chen; Lianhua Yin; Xinhong Wang; Xiaobo Li (Archives of Toxicology, 2017)

Ecto-5′-nucleotidase (CD73) promotes tumor angiogenesis - Li Wang; Shaoxian Tang; Yingjian Wang; Siguang Xu; Jerry Yu; Xiuling Zhi; Zhouluo Ou; Jiayin Yang; Ping Zhou; Zhimin Shao (Clinical & Experimental Metastasis, 2013)

Physiological Characteristics and Leaf Ultrastructure of a Novel Chlorophyll-deficient chd6 Mutant of Vitis venifera Cultured in vitro - Delong Yang; Sheng Li; Mengfei Li; Xiuling Yang; Wangtian Wang; Ziyi Cao; Wei Li (Journal of Plant Growth Regulation, 2012)

Improving cooking and eating quality of Xieyou57, an elite indica hybrid rice, by marker-assisted selection of the Wx locus - Dahu Ni; Shilu Zhang; Sheng Chen; Yong Xu; Li Li; Hao Li; Zongyang Wang; Xiuling Cai; Zefu Li; Jianbo Yang (Euphytica, 2011)

Tomato yellow leaf curl Thailand virus-[Y72] from Yunnan is a monopartite begomovirus associated with DNAβ - Wei Guo; Xiuling Yang; Yan Xie; Xiaofeng Cui; Xueping Zhou (Virus Genes, 2009)

A scheme for pixel-scale aerodynamic surface temperature over hilly land - Wenbin Min; Zhongming Chen; Linsheng Sun; Wenliang Gao; Xiuling Luo; Tingrong Yang; Jian Pu; Guanglun Huang; Xiurong Yang (Advances in Atmospheric Sciences, 2004)